Overhydration Measured by Bioimpedance Spectroscopy and Urinary Serine Protease Activity Are Risk Factors for Progression of Chronic Kidney Disease - Anja Schork; Bernhard N. Bohnert; Nils Heyne; Andreas L. Birkenfeld; Ferruh Artunc (Karger Publishers, 2020)
Background: Overhydration (OH) is common in chronic kidney disease (CKD) and might be related to the excretion of urinary serine proteases. Progression of CKD is associated with proteinuria; however, the interrelations of urinary serine proteases, OH, and progression of CKD remain unclear. Methods: In n = 179 patients with stable nondialysis-dependent CKD of all stages, OH was measured using bioimpedance spectroscopy (Body Composition Monitor; Fresenius), and urinary serine protease activity was determined using the peptide substrate S-2302. After a median follow-up of 5.9 (IQR: 3.9-6.5) years, progression to end-stage renal disease (ESRD) was analyzed retrospectively. Results: OH correlated with baseline MDRD-eGFR, urinary albumin creatinine ratio (ACR), and urinary aprotinin-sensitive serine protease activity. Progression to ESRD occurred in n = 33 patients (19%) and correlated with OH and urinary serine protease activity as well as MDRD-eGFR and ACR. Patients were divided into 2 groups determined by cutoff values from receiver operating characteristics for MDRD-eGFR (32 mL/min/1.73 m2), ACR (43 mg/g creatinine), urinary serine protease activity (0.9 RU/g creatinine), and OH (1 L/1.73 m2). Across these cutoff values, Kaplan-Meier curves for renal survival showed significant separations of the groups. In Cox regression adjusted for MDRD-eGFR, ACR, P-NT-pro-BNP, systolic blood pressure, and diabetes mellitus, patients with OH >1 L/1.73 m2 had a 3.32 (95% CI: 1.26-8.76)-fold higher risk for progression to ESRD. Conclusions: Our results corroborate that OH detected by bioimpedance spectroscopy in CKD patients is an independent risk factor for progression to ESRD in addition to GFR and albuminuria. Urinary serine protease activity is associated with OH and progression of CKD and provides a possible underlying mechanism.